Analisis Ketersediaan Pangan dan Kinerja Penyuluh Pertanian dalam Penyediaan Pangan di Kota Bogor - Haryanto, Yoyon; Pradiana, Wida (Universitas Brawijaya, Indonesia, 2014)
This research is motivated by the condition of the Bogor City residents each year increased density so the impact on the food supply must be provided food institutions Bogor to meet those conditions . It is therefore necessary strategic steps to stimulate and control the availability of food one is to increase the role of agricultural extension as the spearhead of agricultural development in the city of Bogor. The purpose of this research was conducted to analyze the situation of food availability Bogor Year 2011 till 2015 and the role and function of agricultural extension Bogor, in meeting food needs in 2011 until 2015. This study was a cross sectional survey methods to collect secondary data and primary. Based on analysis of population required food availability Bogor for all types of commodities are mostly imported from other regions. Dependency of food imports from other regions to predict the next five years will be even higher, this is due to existing agricultural lands currently only 13% of the total land designation and conversion is likely to happen again for the next five years. Extension workers and extension agencies are located in the city of Bogor as it should have duties that no longer oriented towards increasing production. Auth Bogor Agricultural extension is supposed to maintain existing production (13%) and seeks to diversify into the production of refined by developing farmer groups as a basis for the development of food products. The role of other equally important duties that must be agricultural extension in the area of the city is becoming a mediator and liaison food access, because with good access and availability of food then travel relatively more secure society for people in urban areas tend to be dependent on food-food supply results other areas.